A bibliometric study of sustainable technology research - Morteza Akbari (Taylor & Francis Group, 2020)
Sustainable technology is a rather new subject in sustainability which is paying academics’ attention recently. This article provides a bibliometric review of sustainable technology studies in the sustainability area. Data from the Web of Science (WoS), database relating to 1122 publications available between 1970 and 2019 is used. Numerous bibliometric methods are used to do this indication. The VOSviewer software is used to graph the bibliographic documents. The findings revealed that publications around this area have been enhanced considerably in the last decade and the USA is the most dominant country. Furthermore, the co-citation network of references revealed five clusters; the competitive advantage of environmental innovation, the development of sustainable technologies, environmental policy tools, undesirable output solutions, and innovative environmental activities. This is the initial research toward proposing a bibliometric study of sustainable technology investigation in the sustainability area with definite theoretical and applied consequences.